2013
DOI: 10.4172/2155-9570.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Modified Lipoproteins in Diabetic Retinopathy: A Local Action in the Retina

Abstract: Clinical epidemiological studies have revealed relatively weak, yet statistically significant, associations between dyslipidemia/dyslipoproteinemia and diabetic retinopathy (DR). Recent large interventional studies, however, demonstrated an unexpectedly robust efficacy of fenofibrate on the development of DR, possibly independent of plasma lipids. To unify the apparent discrepancies, we hypothesize that plasma lipoproteins play an indirect but important role in DR, contingent on the integrity of the blood-reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 95 publications
1
11
0
Order By: Relevance
“…1 B). To evaluate the effect of berberine on LDL-cell interactions, we employed N-LDL and HOG-LDL at 200 mg/L, a concentration we consider to be pathophysiologically relevant in DR. 8 Native-LDL did not affect cell viability, while HOG-LDL reduced it by approximately 50% ( Fig. 1 B).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…1 B). To evaluate the effect of berberine on LDL-cell interactions, we employed N-LDL and HOG-LDL at 200 mg/L, a concentration we consider to be pathophysiologically relevant in DR. 8 Native-LDL did not affect cell viability, while HOG-LDL reduced it by approximately 50% ( Fig. 1 B).…”
Section: Resultsmentioning
confidence: 85%
“…Previously we have demonstrated that in people with diabetes, LDL becomes extravasated through leaking BRBs, and subsequently modified by oxidation and glycation even in the ‘preclinical' stages of DR. 4 7 Therefore, we have postulated that in addition to hyperglycemia, extravasation, and modification of plasma lipoproteins, with resultant cytotoxicity, are important drivers of DR. 8 We found that among other adverse effects, modified LDL induces death in several types of human retinal cells. 5 , 6 , 9 Specifically, Müller cell culture studies revealed that modified LDL causes oxidative and endoplasmic reticulum (ER) stresses, and apoptotic death, but the detailed underlying mechanisms of cellular injury are not yet fully understood.…”
mentioning
confidence: 86%
“…The potential mechanism of action of the association between lipids and DR is also unclear. It has been hypothesized that lipoproteins leak through the disrupted blood–retinal barrier and have a cytotoxic effect on retinal cells (Yu & Lyons 2013). Others hypothesized that lipoproteins interact with the activation of protein kinase C and advanced glycation end product formation – two pathways involved in DR pathophysiology (Chang & Wu 2013).…”
Section: Discussionmentioning
confidence: 99%
“…HDL also stimulates production of endothelial nitric oxide and induces anti-apoptotic, anti-inflammatory and anti-thrombotic properties20. Clinical epidemiological studies have demonstrated that dyslipidemia/dyslipoproteinemia is significantly correlated with DR patients21. Serum Apo-B and Apo-B/Apo-A ratio were the most significant metabolic risk factors for PDR22.…”
Section: Discussionmentioning
confidence: 99%